Identification of univalent chromosomes in monosomic lines of cotton (Gossypium hirsutum L.) by means of cytogenetic markers - M. F. Sanamyan; Sh. U. Bobokhujayev (Вавиловский журнал генетики и селекции, 2019)
The lack of clear morphological markers of cotton chromosomes contributed to the development of an unconventional method for marking chromosomes using translocations. Today, tester translocation cotton lines represent the most complete set of cytological markers. The results of cytogenetic analysis of F1 hybrids obtained from crosses of monosomic cotton lines with translocation lines with identified chromosomes are presented. Cytogenetic identification and numbering of univalent chromosomes in 25 monosomic lines of the cytogenetic collection of the National University of Uzbekistan allowed us to establish the following univalent occurrences: chromosome 2 in four monosomic lines, chromosome 4 in 15 lines, chromosome 6 in four lines, chromosome 7 of the At-subgenome in one line and chromosome 18 of the Dt-subgenome in one line. The remaining 21 lines were duplicates of three non-homologous chromosomes. All monosomic lines identified were characterized by differences in univalent sizes, meiotic index, number of tetrads with micronuclei, pollen fertility, frequency of monosomy in the progeny, and a complex of morphological characters associated with the monosomy of the chromosome identified. Despite differences in the genotypic environment and methods for producing monosomics in the two cotton collections, there is a surprising coincidence of data suggesting a higher frequency of chromosomes 2, 4 and 6 occurring as monosomics, while the other chromosomes of the set occur as monosomics at a much lower frequency, and eight nonhomologous chromosomes (5, 8, 13 of the At-subgenome and 14, 15, 19, 22 and 24 of the Dt-subgenome of cotton) never do.